Differentiation of IL-17-Producing Invariant Natural Killer T Cells Requires Expression of the Transcription Factor c-Maf - Yu, Jhang-Sian; Hamada, Michito; Ohtsuka, Shigeo; Yoh, Keigyou; Takahashi, Satoru; Miaw, Shi-Chuen (Frontiers in Immunology, 2017)
c-Maf belongs to the large Maf family of transcription factors and plays a key role in the regulation of cytokine production and differentiation of TH2, TH17, TFH and Tr1 cells. Invariant natural killer T (iNKT) cells can rapidly produce large quantity of TH-related cytokines such as IFN-γ, IL-4 and IL-17A upon stimulation by glycolipid antigens, such as α-galactosylceramide (α-GalCer). However, the role of c-Maf in iNKT cells and iNKT cells-mediated diseases remains poorly understood. In this study, we demonstrate that α-GalCer-stimulated iNKT cells express c-Maf transcript and protein. By using c-Maf-deficient fetal liver cell-reconstituted mice, we further show that c-Maf-deficient iNKT cells produce less IL-17A than their wild-type (WT) counterparts after α-GalCer stimulation. While c-Maf deficiency does not affect the development and activation of iNKT cells, c-Maf is essential for the induction of IL-17-producing iNKT (iNKT17) cells by IL-6, TGF-β and IL-1β, and the optimal expression of RORγt. Accordingly, c-Maf-deficient iNKT17 cells lose the ability to recruit neutrophils into the lungs. Taken together, c-Maf is a positive regulator for the expression of IL-17A and RORγt in iNKT17 cells. It is a potential therapeutic target in iNKT17 cell-mediated inflammatory disease.